2022
DOI: 10.3390/zoonoticdis2030013
|View full text |Cite
|
Sign up to set email alerts
|

Changing Geographic Ranges of Human Biting Ticks and Implications for Tick-Borne Zoonoses in North America

Abstract: Ticks and tick-borne pathogens are increasing public health threats due to emergence of novel pathogens, expanding geographic ranges of tick vectors, changing ecology of tick communities, as well as abiotic and biotic influences on tick–host–pathogen interactions. This review examines the major human-biting ixodid tick species and transmitted pathogens of North America. Topics addressed include current and projected tick geographic ranges, potential risks for introduction of tick transmitted microbes into thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 207 publications
0
7
0
Order By: Relevance
“…Our models support and expand upon previous work on habitat suitability for ticks in Illinois. Records of county-level establishment, passive surveillance, and ecological niche modeling demonstrate expansion of I. scapularis across the state (Eisen et al 2016;Kopsco et al 2021;Alkishe et al 2021;Wikel 2022), however our expectation that as the climate continues to warm, regions in southern and central Illinois will become less hospitable for a desiccant-sensitive species like I. scapularis, was supported. Our models predicted that I. scapularis will be confined to more northern regions in the state, and within habitats that provide more protective cover (e.g.…”
Section: Discussionmentioning
confidence: 72%
“…Our models support and expand upon previous work on habitat suitability for ticks in Illinois. Records of county-level establishment, passive surveillance, and ecological niche modeling demonstrate expansion of I. scapularis across the state (Eisen et al 2016;Kopsco et al 2021;Alkishe et al 2021;Wikel 2022), however our expectation that as the climate continues to warm, regions in southern and central Illinois will become less hospitable for a desiccant-sensitive species like I. scapularis, was supported. Our models predicted that I. scapularis will be confined to more northern regions in the state, and within habitats that provide more protective cover (e.g.…”
Section: Discussionmentioning
confidence: 72%
“…Our models support and expand upon previous work on habitat suitability for ticks in Illinois. Records of county-level establishment, passive surveillance, and ecological niche modeling demonstrate expansion of I. scapularis across the state (Eisen et al 2016;Kopsco et al 2021;Alkishe et al 2021;Wikel 2022), however our expectation that as the climate continues to warm, regions in southern and central Illinois will become less hospitable for a desiccant-sensitive species like I. scapularis, was not supported. We found that occurrence of these species are still driven strongly by precipitation and temperature variables as previous work in the state has demonstrated (Bacon et al 2021), but in ways we did not expect.…”
Section: Discussionmentioning
confidence: 83%
“…Our models support and expand upon previous work on habitat suitability for ticks in Illinois. Records of county-level establishment, passive surveillance, and ecological niche modeling demonstrate the expansion of I. scapularis across the state [ 34 , 67 , 72 , 73 , 74 ]; however, our expectation that as the climate continues to warm, regions in southern and central Illinois will become less hospitable for a desiccant-sensitive species such as I. scapularis was not supported. We found that the occurrence of these species is still driven strongly by precipitation and temperature variables as previous work in the state has demonstrated [ 9 ] but in ways we did not expect.…”
Section: Discussionmentioning
confidence: 94%